Gentrification and Reform Politics in Montréal, 1982 - Ley, David; Mills, Caroline (Cahiers de géographie du Québec, 1986)
Number: 81
Keywords: Gentrification; Réformistes; Élections

Un aperçu féministe sur la restructuration de l'emploi et sur la gentrification: le cas de Montréal - Rose, Damaris (Cahiers de géographie du Québec, 1987)
Number: 83
Keywords: Femmes; Féminisme; Gentrification; Logement

La gentrification à Montréal 1971-1991 - Métaireau, Béatrice (Études canadiennes / Canadian Studies, 1999)
Number: 46
Keywords: Logement; Quartiers

Le Village gai. Les paradoxes de la visibilité - Giraud, Colin (Montréal : la cité des cités, 2017)
Keywords: Gentrification; Quartiers

Cogentrification sociale et économique: la colocalisation de la main-d'oeuvre et des emplois de services aux entreprises à Montréal, 1996-2001 - Naud, Daniel; Apparicio, Philippe; Shearmur, Richard (Cahiers de géographie du Québec, 2009)
Plusieurs études se sont penchées sur l'évolution de la localisation des emplois de services aux entreprises. Une hypothèse qui n'a pas encore été pleinement explorée est celle selon laquelle ce secteur chercherait à s'implanter à proximité des quartiers résidentiels où réside sa main-d'oeuvre. Notre étude démontre qu'il semble effectivement y avoir une certaine colocalisation, mais que celle-ci affecte principalement la main-d'oeuvre résidant à proximité du centre-ville. Ici, on trouve que les nouveaux emplois de services aux entreprises tendent à se localiser à proximité des quartiers déjà habités par leurs employés. Ceci nous permet d'avancer l'hypothèse d'une cogentrification : d'abord résidentielle, alors que certains professionnels se sont, depuis une vingtaine d'années, réapproprié des quartiers péricentraux de Montréal. Ensuite économique, tandis que les emplois de bureau en services aux entreprises se sont localisés vers ces mêmes quartiers. Many studies are currently investigating the localization of business services jobs and its development. One hypothesis, which has been insufficiently researched to date, is that this sector tends to locate in the vicinity of residential neighbourhoods where its workforce lives. This study demonstrates that though colocalization does exist to some extent, it mainly affects workers living close to the downtown area. It has been discovered that new business services jobs tend to locate in close proximity to areas already inhabited by employees in the business services sector. We can therefore hypothesize that cogentrification is primarily residential. A number of professional workers have returned to live in Montreal's pericentral neighbourhoods over the past twenty years. Cogentrification is also economic, insofar as business services office jobs have gravitated toward these same areas during the same period.
Number: 149
Keywords: Gentrification; Quartiers; Travail

Pauvreté et richesse dans la région montréalaise depuis l'après-guerre. Un paysage en mouvement - Séguin, Anne-Marie; Negron-Poblette, Paula; Apparicio, Philippe (Histoire de Montréal et de sa région, 2012)
Keywords: Gentrification; Pauvreté; Quartiers

David Marvin’s Griffintown: An archival exploration of a ghosted neighbourhood - Fleming, Arwen Jean (Université Concordia, 2015)
Keywords: Gentrification; Griffintown; Quartiers

Poverty and Wealth in the Post-War Montreal Area: A Landscape in Motion - Séguin, Anne-Marie; Negron, Paula; Apparicio, Philippe (Montreal: The History of A North American City, 2018)
Keywords: Gentrification; Pauvreté; Quartiers

Du bagel au yoga de luxe. Consommer un vivre-ensemble imaginé rue Saint-Viateur - Désilets, Gabrielle (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Gentrification; Mile End; Quartiers

La mixité sociale programmée en milieu résidentiel à l’épreuve des discours critiques internationaux: le cas de Hochelaga-Maisonneuve à Montréal - Germain, Annick; Rose, Damaris (Lien social et Politiques, 2010)
issued: 2010-21-00
Keywords: Gentrification; Hochelaga (quartier); Maisonneuve (quartier); Pauvreté; Quartiers

It Took a Tenants' Movement: Tenants and the Making of Habitations Jeanne-Mance (1959-1994) - Nettling, Pierson Christopher (Université Concordia, 2017)
Keywords: Drapeau; Jean; Gentrification; Groupes populaires; Logement; Maires; Quartiers; Saint-Jacques

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail